Benchmarking as a foundation of the future economy - Andreevich, Berezin Artiom (Cambridge Scholars Publishing, 2020)
This book explores how to increase the efficiency of decision-making for enterprise management and increase its competitiveness based on mathematical modeling of the benchmarking process, predictive modeling of the dynamics of economic performance indicators, and the synthesis and selection of development strategies using software tools. It argues that, instead of mutually devouring competition, which is common in the modern world, the model of friendly cooperative benchmarking on the principle of 'win-win' is proposed for consideration. The advantage of this principle over the classic competi.